2021
DOI: 10.3390/cancers13123017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of KIF11 and KIF14 Expression in Pancreatic Adenocarcinoma

Abstract: Available biomarkers for pancreatic adenocarcinoma (PAC) are inadequate to guide individual patient prognosis or therapy. Therefore, herein we aimed to verify the hypothesis that differences in the expression of KIF11 and KIF14, i.e., molecular motor proteins being primarily implicated in cell division events could account for the differences in the clinical outcome of PAC patients. In-house immunohistochemistry was used to evaluate the protein expressions of KIF11 and KIF14 in PAC, whereas RNA-seq datasets pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Indeed, in contrast to KIF11 protein, high KIF11 mRNA was associated with noticeably better OS and constituted an independent predictor of improved OS in the TCGA cohort. This finding contradicts the reported poor prognosis of ovarian, pancre-atic, breast or non-small cell lung cancer patients overexpressing KIF11 mRNA [20,[24][25][26]. Nevertheless, given that protein levels equate more closely with function than mRNA levels [27], it is likely that elevated KIF11 expression is functionally linked to an adverse prognosis in CRC.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Indeed, in contrast to KIF11 protein, high KIF11 mRNA was associated with noticeably better OS and constituted an independent predictor of improved OS in the TCGA cohort. This finding contradicts the reported poor prognosis of ovarian, pancre-atic, breast or non-small cell lung cancer patients overexpressing KIF11 mRNA [20,[24][25][26]. Nevertheless, given that protein levels equate more closely with function than mRNA levels [27], it is likely that elevated KIF11 expression is functionally linked to an adverse prognosis in CRC.…”
Section: Discussionmentioning
confidence: 80%
“…This was because various staining intensities are frequently observed in clinical practice, and these may have a biological meaning. Indeed, our recent pancreatic cancer data on KIF11 has revealed that the IRS scoring system was more informative for prognosis than PS itself [ 20 ]. Importantly, in our studies, we avoided choosing arbitrary cut-off values for the interpretation of target protein expression, and therefore we adopted outcome data-derived method from the Evaluate Cutpoint software [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural cell adhesion molecule one ( NCAM1 ) has not been extensively investigated in BCa, but there are studies that link its expression with drug resistance in acute myeloid leukemia [ 138 ], pleuropulmonary blastoma [ 139 ], and cervical intraepithelial neoplasia [ 140 ]. Kinesin family member 14 ( KIF14 ) expression levels were linked to chemosensitivity of hepatocellular carcinoma [ 141 ] and cervical cancer [ 142 ], as well as to prognosis of various cancers, such as breast [ 143 ] and pancreatic cancer [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the role of KIF14 expression in gastrointestinal cancer, only a few studies have reported this issue. For instance, Previous studies indicated that KIF14 is positively associated with aggravating disease features and its high expression is associated with worse survival in patients with gastric cancer and pancreatic adenocarcinoma ( 16 , 17 ). Additionally, upregulation of KIF14 has also been found to be associated with the elevated tumor stage and pathological tumor grade of patients with hepatocellular carcinoma (HCC) ( 18 ).…”
Section: Introductionmentioning
confidence: 99%